The Influence Of Green Accounting, Environmental Performance, And Firm Size On Profitability In Energy Firms - Nur Adha, Bintang Prayudha; Fitriyani, Lita Yulita (JAS (Jurnal Akuntansi Syariah), 2025)
This research aims to test the influence of green accounting, environmental performance, and firm size on profitability. The population of this research is banking companies listed on the Indonesia Stock Exchange for the period 2019-2023. The study uses a quantitative approach with secondary data obtained from sustainability reports and annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2019–2023. The population consists of 55 company in 2019, 57 company in 2020, 63 company in 2021, 65 company in 2022, and 73 company in 2023, with a total of 105 observations selected using purposive sampling. Data analysis was conducted using multiple linear regression with the help of IBM SPSS version 25. The research results show that green accounting and firm size has an influence on profitability, while environmental performance do not have an influence on profitability.